Forgetting of competing solutions as a consequence of analogical problem-solving attempts. Issue 8 (14th September 2021) - George, Tim; Wiley, Jennifer
ABSTRACT : Three experiments used a paradigm based on Retrieval-Induced Forgetting research to test for the competition from non-useful sources of information in cross-domain analogical transfer. This was accomplished by presenting people with texts introducing multiple candidate solutions prior to attempting the Radiation problem, and later testing memory for the texts. In Experiment 1, viable and unviable candidate solutions that varied in surface and structural similarity were presented in their own story contexts. In Experiments 2 and 3, the viable and unviable solutions were embedded within the same story context. The results suggest that forgetting unviable solutions that share surface-level overlap with the target problem may be less important than suggested by prior work. Instead, greater evidence of forgetting was obtained when unviable solutions were embedded within the same context as viable solutions. These findings suggest that competition from superficially similar, unviable solutions may not be the main obstacle during analogical problem-solving attempts, but rather the main obstacle for transfer may be the selection of relevant solution concepts.